The Teratogenic Effect of The Mindi (Melia azedarach L) Leaves Ethanol Extract on Mice (Mus musculus) Fetus - Adisti Erlina Sutomo; Trully D. Sitorus; Adhi Pribadi (Althea Medical Journal, 2015)
Background: Mindi leaves (Melia azeradach L.) were used by Indonesians as a traditional medicine for pregnant women because it was considered to be safe. Mindi leaves contain several active compounds and one of them is suspected as a teratogen and can disrupt fetus growth in gestation. This research aims to know about the teratogenic effect of ethanol extract of Mindi leaves by using mice.Methods: This was a laboratory experimental study using 27 pregnant female mice (Mus musculus) of Swiss Webster strain which were randomly assigned to 3 groups (n=9) controlled (Carboxymethyl cellulose 1% for day 1–18 of pregnancy), group I (mindi leaves ethanol extract 3.22 mg+Carboxymethyl cellulose 1% day 1–5 of pregnancy), and group II (mindi leaves ethanol extract 3.22 mg+Carboxymethyl cellulose 1% day 6–18 of pregnancy). Observation was done to see total amount of fetus, live normal fetus count, length and weight of fetus, abnormal fetus count consisting of dead fetus count with normal and abnormal external morphology, and resorbed fetus count. This research was done from October to November 2012 in Pharmacological laboratory of Faculty of Medicine Universitas Padjajdjaran. Data analysis utilized unpaired t-test.Results: The result showed a significant difference (p<0.05), seen from live normal fetus count and abnormal fetus count consisting of dead fetus count with normal and abnormal external morphology, and resorpted fetus count. Conclusions: Administration of Mindi leaves extract during pregnancy of mices can cause teratogenic effect.[AMJ.2015;2(1):221–25]